Seismic Performance Evaluation of Story Drift-Based Fluid Viscous Damper Configurations - Windra Pranoto Simatupang; Data Iranata (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Indonesia is located in one of the world's most seismically active regions, requiring high-rise buildings to be designed with adequate seismic resistance to control excessive lateral deformation and prevent structural instability caused by the P–Δ effect. This study evaluates the seismic performance of a multi-story building equipped with different Fluid Viscous Damper (FVD) configurations using Nonlinear Time History Analysis (NLTHA). Three structural models were investigated: a bare frame structure without dampers (Model A), a structure with uniformly distributed FVDs (Model B), and a structure with FVDs installed only at stories experiencing the largest inter-story drifts (Model C). Three scaled historical earthquake records—Imperial Valley, Loma Prieta, and Northridge—were employed according to the seismic requirements of SNI 1726:2019. The results demonstrate that Model A exceeded the allowable inter-story drift limits at several critical stories. Although Model B produced the greatest drift reduction, it significantly increased structural stiffness because of the extensive bracing system. In contrast, Model C effectively reduced inter-story drift to within the allowable limits while maintaining greater structural flexibility. These findings indicate that strategically placing FVDs at critical stories provides a more efficient seismic mitigation strategy than conventional uniform damper installation.